Effect of long-period stacking ordered phase on microstructure, mechanical property and corrosion resistance of Mg alloys: A review - Daokui Xu (Progress in Natural Science: Materials International, 2016)
Magnesium alloys containing long period stacking ordered (LPSO) phase have been received a great deal of attention in the last decade owing to their excellent comprehensive properties of mechanical strength and corrosion resistance. In this paper, some fundamental aspects of LPSO containing Mg alloys have been reviewed, including: (1) microstructural characterization, formation conditions and the associated phase transformation of LPSO phases in Mg alloys; (2) deformation mechanism of LPSO phases and their influence on the deformation mechanism of the Mg matrix; (3) effect of LPSO structure on the mechanical performance such as tensile strength, creep resistance, fracture toughness and fatigue strength; (4) corrosion behavior of LPSO containing Mg alloys and their possible applications as the biomaterials. Moreover, some remaining unsolved issues of the LPSO containing Mg alloys and the future target about how to further improve their service properties have been also described.